Soroprevalência entre as Mesorregiões. Análise das soro positividades dos animais amostrados de criatórios nas mesorregiões de Minas Gerais- MG, 2016. - Jessica Carolina Reis Barbosa (2020)
Sanitary problems, especially enteric problems, are responsible for major economic impacts on pig production. Lawsonia intracellularis etiological agent of swine proliferative enteropathy, being an important agent that causes diarrhea in the final stages of the production system, and in several animal species. The presence / circulation of this microorganism in pig backyard farms in of Minas Gerais is unknown and can be an important factor in the maintenance of this agent in tecnified swine herds of state. To determine the serological profile and the seroprevalence of anti-L intracellularis antibodies. in pig subsistence farms in Minas Gerais, 288 farms were sampled, obtaining 1100 samples. In these herds, serum samples were obtained from animals of different ages and subsequently analyzed by the immunoperoxidase technique in cell monolayers. The general prevalence for anti-L. intracellularis antibodies in Minas Gerais was 97.53% and there was no statistical difference between the prevalence of the sampled mesoregions. Anti-L. intracellularis were present in all investigated farms in Minas Gerais, indicating wide circulation of the agent in this type of property in the state.